Beyond the business case for agricultural value chain development: An economywide approach applied to Egypt - Breisinger, Clemens; Raouf, Mariam; Thurlow, James; Wiebelt, Manfred (International Food Policy Research Institute, 2019)
This paper goes beyond the “business” case for agricultural value chain development and presents an economy-wide framework to make the “development” case. We show that there are several key transmission channels that determine the economy-wide impacts of promoting various value chains, including forward and backward economic linkages, price responses, and net employment effects. These impacts all matter for household incomes, poverty, and dietary diversity. Results for Egypt show that agricultural value chain development generates economy-wide growth as well as growth in the agri-food system, but the impacts on employment suggest that agricultural growth can create new (and better) jobs in and beyond the agri-food system, but not necessarily more jobs. The results also show that productivity-driven agricultural growth in all crops is pro-poor and improves nutrition. However, potential adverse effects of livestock-led growth show that growth acceleration in single sectors can be negative, highlighting the importance of a systems analysis or, in our case, an economy-wide analysis. It is clear that no single sub-sector is best at achieving all the development outcomes examined. Moreover, the ranking of value chains by their development outcomes differs across sub-national regions. As such, results from this paper may provide useful decision support for the government and its development partners to select value chains depending on their priority development outcomes.